WEBVTT
00:00:02.160 --> 00:00:10.720
Calculate the definite integral from zero to two of three π₯ cubed plus two π₯ multiplied by three π₯ to the fourth power plus four π₯ squared with respect to π₯.
00:00:12.880 --> 00:00:19.400
Now, looking at the integrand, thatβs the expression weβve been asked to integrate, we can see that it is the product of two polynomials.
00:00:19.880 --> 00:00:22.880
There are, in fact, two methods that we could use to answer this question.
00:00:23.200 --> 00:00:25.880
So, weβll look at them both.
00:00:25.880 --> 00:00:36.440
As neither of these polynomials is raised to a power other than one, itβs actually quite straightforward to just distribute the parentheses to give a new polynomial, which we can then integrate term by term.
00:00:37.680 --> 00:00:40.000
So, thatβs what weβll do in our first method.
00:00:40.200 --> 00:00:46.560
Distributing the parentheses and remembering that we add the exponents when multiplying two polynomial terms together.
00:00:46.840 --> 00:00:58.240
We have that our integral is equal to the definite integral from zero to two of nine π₯ to the seventh power plus 12π₯ to the fifth power plus six π₯ to the fifth power plus eight π₯ cubed with respect to π₯.
00:00:59.640 --> 00:01:06.920
We can then combine the like terms and simplify integrand to nine π₯ to the seventh power plus 18π₯ to the fifth power plus eight π₯ cubed.
00:01:08.360 --> 00:01:21.080
We then recall that to integrate the general polynomial term ππ₯ to the power of π for real values of π and π where π is not equal to negative one, we increase the exponent by one and divide by the new exponent.
00:01:21.080 --> 00:01:28.200
Giving ππ₯ to the power of π plus one over π plus one plus the constant of integration π if itβs an indefinite integral.
00:01:28.680 --> 00:01:32.040
Although our integral has limits, itβs a definite integral.
00:01:32.040 --> 00:01:34.720
So, we donβt need to worry about constants of integration here.
00:01:35.960 --> 00:01:48.080
Applying this rule and integrating term by term then, we have that this integral is equal to nine π₯ to the eighth power over eight plus 18π₯ to the sixth power over six plus eight π₯ to the fourth power over four.
00:01:48.320 --> 00:01:51.280
And thatβs all evaluated between the limits of zero and two.
00:01:52.560 --> 00:01:56.200
Before substituting the limits, we can simplify some of the coefficients.
00:01:56.200 --> 00:02:01.240
In the second term, we have a coefficient of 18 over six, which simplifies to three.
00:02:01.240 --> 00:02:05.880
And in the third term, we have a coefficient of eight over four, which simplifies to two.
00:02:05.880 --> 00:02:12.840
So, our expression becomes nine π₯ to the eighth power over eight plus three π₯ to the sixth power plus two π₯ to the fourth power.
00:02:14.240 --> 00:02:22.960
Substituting our limits then, we have nine multiplied by by two to the eighth power over eight plus three multiplied by two to the sixth power plus two multiplied by two to the fourth power.
00:02:23.160 --> 00:02:26.200
And then, we know that when we substitute zero, we will just get zero.
00:02:26.440 --> 00:02:29.600
So, weβre subtracting zero for the lower limit.
00:02:30.880 --> 00:02:38.240
Evaluating on a calculator gives 288 plus 192 plus 32, which all sums to 512.
00:02:39.080 --> 00:02:52.040
So, by distributing the parentheses to give a polynomial and then recalling how to integrate a general polynomial term where the exponent is not equal to negative one, weβve calculated the value of this definite integral to be 512.
00:02:54.080 --> 00:02:56.800
Now, there is another method that we could use.
00:02:56.800 --> 00:03:04.000
And in order to use this method, we need to spot that there is a connection between the expressions inside each set of parentheses.
00:03:05.360 --> 00:03:16.960
If we find the derivative of the expression in the second set of parentheses, thatβs three π₯ to the fourth power plus four π₯ squared, we find that itβs equal to 12π₯ cubed plus eight π₯.
00:03:16.960 --> 00:03:23.560
And if we factor by four, we then see that this is an exact multiple of the expression inside the first set of parentheses.
00:03:24.840 --> 00:03:30.080
This suggests that we could also solve this problem by using integration by substitution.
00:03:30.080 --> 00:03:31.680
Letβs have a look at what that would look like.
00:03:33.080 --> 00:03:41.840
We introduce a new variable, which weβll call π’, to be that part of the expression whose derivative, or a scale multiple of it, also appears in the integrand.
00:03:41.840 --> 00:03:45.160
So, π’ is equal to three π₯ to the fourth power plus four π₯ squared.
00:03:46.640 --> 00:03:56.680
Weβve just seen that the derivative of this expression, so thatβs now dπ’ by dπ₯, is equal to 12π₯ cubed plus eight π₯, which we can write as four multiplied by three π₯ cubed plus two π₯.
00:03:58.360 --> 00:04:03.240
Now, dπ’ by dπ₯ is not a fraction, but we can treat it a little like one.
00:04:03.240 --> 00:04:09.680
So, itβs equivalent to say that one-quarter dπ’ is equal to three π₯ cubed plus two π₯ dπ₯.
00:04:10.120 --> 00:04:11.160
Now, why is this helpful?
00:04:11.840 --> 00:04:19.440
Well, if we look back at the original integrand, we can see that three π₯ to the fourth power plus four π₯ squared is what we defined to be π’.
00:04:20.040 --> 00:04:27.000
And three π₯ cubed plus two π₯ dπ₯ is what weβve just seen to be equal to one-quarter dπ’.
00:04:27.560 --> 00:04:33.520
So, we know how to change everything inside our integral from being in terms of π₯ to being in terms of π’.
00:04:35.040 --> 00:04:38.440
What we must also remember, though, is that we have a definite integral.
00:04:38.440 --> 00:04:44.640
So, we also need to change our limits of zero and two from limits in terms of π₯ into limits in terms of π’.
00:04:46.200 --> 00:04:49.880
We do this using the equation we already have connecting π₯ and π’.
00:04:50.400 --> 00:04:57.560
When π₯ is equal to zero, π’ is equal to three multiplied by zero to the fourth power plus four multiplied by zero squared, which is equal to zero.
00:04:59.080 --> 00:05:07.160
And when π₯ is equal to two, π’ is equal to three multiplied by two to the fourth power plus four multiplied by two squared, which is equal to 64.
00:05:07.440 --> 00:05:11.880
So, the limits for our integral in terms of π’ are zero and 64.
00:05:13.400 --> 00:05:16.040
Letβs now change this integral to be in terms of π’.
00:05:16.520 --> 00:05:19.840
We have the definite integral between zero and 64.
00:05:20.600 --> 00:05:24.600
Three π₯ to the fourth power plus four π₯ squared becomes π’.
00:05:24.600 --> 00:05:28.520
And three π₯ cubed plus two π₯ dπ₯ becomes one-quarter dπ’.
00:05:28.840 --> 00:05:36.800
We can rewrite that factor of one-quarter in front of π’ or even bring it out to the front of the integral if we wish.
00:05:36.800 --> 00:05:43.840
And we find that our integral has now become the integral from zero to 64 of one-quarter π’ with respect to π’.
00:05:44.040 --> 00:05:46.280
Now, this is just the integral of a polynomial term.
00:05:46.280 --> 00:05:49.240
So, we can apply the same rule that we already used.
00:05:50.640 --> 00:06:00.680
We increase the exponent by one to give π’ squared and divide by the new exponent to give one-quarter multiplied by a half π’ squared, evaluated between zero and 64.
00:06:02.160 --> 00:06:03.920
The coefficient simplifies to one-eighth.
00:06:04.120 --> 00:06:10.520
And then substituting our limits, we have one-eighth of 64 squared minus one-eighth of zero squared, which is just zero.
00:06:11.080 --> 00:06:17.360
And then once again, evaluated on a calculator, we find that this integral is equal to 512.
00:06:18.960 --> 00:06:26.480
So, by either distributing the parentheses and then integrating term by term or using the method of integration by substitution.
00:06:26.680 --> 00:06:37.720
Weβve calculated that the definite integral from zero to two of three π₯ cubed plus two π₯ multiplied by three π₯ to the fourth power plus four π₯ squared with respect to π₯ is equal to 512.